Cross-cultural translation and validation of the Brief Autism Mealtime Behavior Inventory (BAMBI-M) in Malay - Ahmad Zamir, Che Daud; Md Tajuddin, Nor Ermalina Hanita; Mohd Nayan, Noor Aziella; Alrashdi, Mohammed; Mohamad Sabri, Mohamad Qayum; Hosshan, Hasrul (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The Brief Autism Mealtime Behavior Inventory (BAMBI) is extensively utilized for evaluating feeding challenges among children with autism spectrum disorder (ASD). However, its absence in Malay restricts its application within Malaysia. This study aimed to translate and validate the Malay version of BAMBI (BAMBI-M), ensuring both linguistic and conceptual appropriateness for Malay-speaking populations. Methods: The translation followed a structured protocol involving forward and backward translations, reviews by experts and parents, and comprehensive psychometric evaluations. Ten experts and ten parents assessed content and face validity. A total of 180 parents participated in the psychometric validation stage, comprising 90 parents of children with ASD and 90 parents of typically developing children. Reliability was determined through internal consistency using Cronbach’s alpha, test-retest reliability, and validity was confirmed through known-groups analysis. Results: Content validity demonstrated robust agreement among experts, and face validity assessments confirmed item relevance through favorable item impact scores. The internal consistency of BAMBI-M showed excellent reliability, with a Cronbach’s alpha of 0.97. Test-retest reliability coefficients ranged from 0.82 to 0.89, confirming temporal stability. Known-groups validity indicated significant differences between the scores of children with ASD and typically developing children (p < 0.001). Conclusions: BAMBI-M is a reliable and valid instrument for evaluating feeding difficulties in Malaysian children with ASD. Future research should further investigate additional psychometric properties and explore the scale’s applicability across diverse Malaysian populations.